Biotization of In Vitro Plants with Endophytic Beneficial Bacterium (PGP_invit) to Understand Plant-bacteria Interaction - Turkolmez, Nil; Albayrak, Merve; Batool, Maria; Kayihan, Doga Selin; Ekinci, Hamit; Akkaya, Ozlem; Seker, Mine Gul (Springer, 2019)
[No abstract available]